Ring Based Planar Crossover for Beamforming Networks. (2016) - Jayakrishnan, V.M.; Menon, Sreedevi K.
Abstract: A crossover maintains signal integrity when transmission lines overlap. In this paper, a microstrip patch is used to design the overlapping region thus providing desired isolation and transmission between desired ports. Square and Circular patch configurations for crossovers are analysed using ANSYS HFSS. The basic microstrip patch is further modified by introducing fractals enhancing the electrical length and improving the crossover characteristics.